2021
DOI: 10.5194/isprs-archives-xlvi-4-w5-2021-113-2021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Assessment of Digital 3d Models Obtained by Drone-Based Lidar and Drone Imagery

Abstract: Abstract. The purpose of this study is to assess the potential of drone airborne LiDAR technology in Morocco in comparison with drone photogrammetry. The cost and complexity of the equipment which includes a laser scanner, an inertial measurement unit, a positioning system and a platform are among the causes limiting its use. Furthermore, this study was motivated by the following reasons: (1) Limited number of studies in Morocco on drone-based LiDAR technology applications, (2) Lack of study on the parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…They produced a 3D model of the entire area including terrain, buildings, and other details. The other study by Bouziani et al (2021) assessed and confirmed the high accuracy of data from LiDAR (Light Detection and Ranging) drone and photogrammetric drone. Based on this work, it is possible to get high-accuracy fusion-based 3D model from these technologies.…”
Section: Introductionmentioning
confidence: 64%
“…They produced a 3D model of the entire area including terrain, buildings, and other details. The other study by Bouziani et al (2021) assessed and confirmed the high accuracy of data from LiDAR (Light Detection and Ranging) drone and photogrammetric drone. Based on this work, it is possible to get high-accuracy fusion-based 3D model from these technologies.…”
Section: Introductionmentioning
confidence: 64%
“…In recent years, with the advancement in AI, high-resolution image sensors, and UAVs, photogrammetry has become an economical way for obtaining centimeter-resolution 3D models of buildings, infrastructure, and small objects ( 79 ). Common photogrammetric surveys are developed based on the principle of 3D reconstruction from multiple images and structure-from-motion.…”
Section: Review Of 3d Data Sourcesmentioning
confidence: 99%